2010
DOI: 10.1007/s00005-009-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Heparanase in Diseases of the Glomeruli

Abstract: The glomerular basement membrane (GBM) is a kind of net that remains in a state of dynamic equilibrium. Heparan sulfate proteoglycans (HSPGs) are among its most important components. There are much data indicating the significance of these proteoglycans in protecting proteins such as albumins from penetrating to the urine, although some new data indicate that loss of proteoglycans does not always lead to proteinuria. Heparanase is an enzyme which cleaves beta 1,4 D: -glucuronic bonds in sugar groups of HSPGs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 134 publications
(164 reference statements)
2
34
0
2
Order By: Relevance
“…Although other heparanase-related factors (i.e., HS degradation in the GBM, altered interactions between glomerular cells and GBM, or release of HS-bound bioactive molecules) (16,17) may also contribute to DN development, our recent observations unravel what we believe to be a previously unrecognized combinatorial circuit of heparanasedependent molecular events powering chronic inflammation and kidney injury in individuals with DN (Fig. 5).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Although other heparanase-related factors (i.e., HS degradation in the GBM, altered interactions between glomerular cells and GBM, or release of HS-bound bioactive molecules) (16,17) may also contribute to DN development, our recent observations unravel what we believe to be a previously unrecognized combinatorial circuit of heparanasedependent molecular events powering chronic inflammation and kidney injury in individuals with DN (Fig. 5).…”
Section: Discussionmentioning
confidence: 78%
“…While both causal involvement of heparanase in DN and the molecular mechanism underlying heparanase induction by hyperglycemic conditions/diabetic mediators were previously described by the present authors and others (11)(12)(13), the exact mode of heparanase action in DN pathogenesis has not been fully elucidated. Apart from heparanase-mediated loss of HS in the GBM, it was suggested that heparanase contributes to the development of DN by inducing changes in glomerular cell-GBM interactions due to the loss of HS; through the release of HS-bound growth factors, cytokines, and bioactive HS fragments in glomeruli; or by activating signaling cascades that alter cell properties and lead to proteinuria (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be pointed out that the reversal of downregulated nephrin and podocin mRNA/protein by PTX was not complete, which likely accounted for residual proteinuria and nephrinuria despite treatment. In addition, alterations in other elements of the glomerular filtration barrier, such as the endothelial syndecan-4 and glypican-1, and the glycosaminoglycan degrading hyaluronidase and heparanase, have been shown to participate in the development of proteinuria (5,(44)(45)(46). Because transcriptional regulation of these genes was not likely TNF-α-or TGF-β-dependent (47,48), PTX might not be able to modulate the dysregulated mRNA expression as seen in the present model.…”
Section: Discussionmentioning
confidence: 74%